Natural pseurotins and analogs thereof inhibit activation of B-cells and differentiation into the plasma cells - Vašíček, Ondřej; Fedr, Radek; Skoroplyas, Svitlana; Chalupa, David; Sklenář, Matěj; Tharra, Prabhakara Rao; Švenda, Jakub; Kubala, Lukáš (Phytomedicine, 2020)
BACKGROUND: The frequency of allergic diseases is constantly rising. Dysregulated production of isotype E immunoglobulins is one of the key factors behind allergic reactions and its modulation is therefore an important target for pharmacological intervention. Natural products of the pseurotin family were reported to be inhibitors of IgE production in B-cells. Mechanistic details underlying these effects are however not well understood. PURPOSE: In the present study, we synthesized new analogs of natural pseurotins and extensively investigated their inhibitory effects on activation, proliferation and differentiation of B-cells, as well as on the production of IgE. STUDY DESIGN: Effects of two natural pseurotins (pseurotins A and D) and a collection of fully synthetic pseurotin analogs were studied on mouse B-cells stimulated by the combination of IL-4 and E. coli lipopolysaccharide. The IgE production was determined along with cell viability and cell proliferation. The phosphorylation of selected members of the STAT transcription factor family was subsequently investigated. Finally, the in vivo effect of pseurotin D on the ovalbumin-induced delayed type hypersensitivity response was tested in mice. RESULTS: We discovered that several fully synthetic pseurotin analogs were able to decrease the production of IgE in stimulated B-cells with potency comparable to that of pseurotins A and D. We found that the two natural pseurotins and the active synthetic analogs inhibited the phosphorylation of STAT3, STAT5 and STAT6 proteins in stimulated B-cells, resulting in the inhibition of B-cell proliferation and differentiation into the plasma cells. In vivo, pseurotin D decreased ovalbumin-induced foot pad edema. CONCLUSION: Our results advance the current mechanistic understanding of the pseurotin-induced inhibition of IgE production in B-cells by linking the effect to STAT signaling, and associated modulation of B-cell proliferation and differentiation. Together with our finding that structurally simpler pseurotin analogs were able to reproduce the effects of natural pseurotins, the presented work has implications for the future research on these secondary metabolites in the context of allergic diseases.
Keywords: buněčná diferenciace; Phosphorylation; transkripční faktory STAT; STATs; imunoglobulin E; Immunoglobulins; lipopolysacharidy; fosforylace; Lipopolysaccharides; Edema; Escherichia coli; plazmatické buňky; zvířata; Plasma Cells; Lymphocyte Activation; Plasma cell; myši inbrední C57BL; B-lymfocyty; IgE; Ovalbumin; aktivace lymfocytů; Pyrrolidinones; Male; edém; B-Lymphocytes; Cell Differentiation; Mice, Inbred C57BL; imunoglobulin M; Animals; Lymphocyte; mužské pohlaví; ovalbumin; STAT Transcription Factors; pyrrolidinony; Immunoglobulin M; Immunoglobulin E; Pseurotins